The boarding Madrasah Aliyah Religious Program curriculum management by building religious character - Hilal Najmi; Iim Wasliman; Hanafiah Hanafiah; Faiz Karim Fatkhullah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Reinforcement of the boarding schoolin building religious character is really needed to produce graduates with good religious character. This qualitative study aimed at explaining theplanning, organizing, staffing, briefing, coordinating, reporting, budgeting, and supervising on management of boarding MAPK curriculum in building religious character of MAN 4 Banjar students. The results that the management of the MAPK curriculum has been carried out by involving various parties, and is guided by the Ministerial Regulation of Religious Affairs, but still has not had an impact on the religious character of students, it needs efforts to overcome constraints faced by management o by structuring the curriculum specifically applied to boarding activities. This article provides an overview how to build religious character in boarding school. This article contributes to all principals where they would apply boarding school system attributed with the building religious character.